World experience of land relations (Economics and region, 2016)
The given article represents analyzing and evaluating world experience in land relations development including rural appraising. The analyses of the mentioned experience and its implementation in Ukraine provide effective land relations formation.
Keywords: land relations; land assessment; land market; rent; land rentals